Keterlibatan Orang Tua dalam Mengembangkan Empati dan Keterampilan Sosial Anak Usia Dini di Era Digital - Tika Wahyuningtyas; Itsnaini Muslimati Alwi (MASALIQ, 2026)
The development of empathy and social skills in early childhood is an important aspect in forming social-emotional abilities as a foundation for children’s future lives. However, the development of these two aspects faces various challenges, such as reduced social interaction due to gadget use and declining quality of interaction between children and parents. This study aims to analyze the forms of parental involvement and their implications for the development of empathy and social skills in early childhood at KB Kasih Bunda. This study used a qualitative approach with a descriptive research design. The research subjects consisted of parents, teachers, and early childhood children selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The results show that parental involvement is manifested through positive communication, emotional attention, assistance in children’s activities, modeling of social behavior, and habituation of prosocial attitudes. This involvement has implications for the development of children’s empathy, as shown through behaviors such as helping friends, showing concern, and comforting friends who are sad. In addition, children’s social skills develop through the ability to cooperate, share, communicate, and resolve simple conflicts. The conclusion of the study affirms that parental involvement plays an important role in supporting the development of empathy and social skills in early childhood. The implications of this study provide theoretical contributions to the development of early childhood education studies, particularly in the social-emotional aspect, as well as practical implications for parents, teachers, and early childhood education institutions in building family-school synergy to create an environment that optimally supports children’s social-emotional development.